Fingerprinting Blue Carbon: Rationale and Tools to Determine the Source of Organic Carbon in Marine Depositional Environments - Geraldi, Nathan R.; Ortega, Alejandra; Serrano, Oscar; Macreadie, Peter I.; Lovelock, Catherine E.; Krause-Jensen, Dorte; Kennedy, Hilary; Lavery, Paul S.; Pace, Michael L.; Kaal, Joeri; Duarte, Carlos M. (Frontiers in Marine Science, 2019)
Blue carbon is the organic carbon in oceanic and coastal ecosystems that is captured on centennial to millennial timescales. Maintaining and increasing blue carbon is an integral component of strategies to mitigate global warming. Marine vegetated ecosystems (especially seagrass meadows, mangrove forests, and tidal marshes) are blue carbon hotspots and their degradation and loss worldwide have reduced organic carbon stocks and increased CO2 emissions. Carbon markets, and conservation and restoration schemes aimed at enhancing blue carbon sequestration and avoiding greenhouse gas emissions, will be aided by knowing the provenance and fate of blue carbon. We review and critique current methods and the potential of nascent methods to track the provenance and fate of organic carbon, including: bulk isotopes, compound-specific isotopes, biomarkers, molecular properties, and environmental DNA. We find that most studies to date have used bulk isotopes to determine provenance, but this approach often cannot distinguish the contribution of different primary producers to organic carbon in depositional marine environments. Based on our assessment, we recommend application of multiple complementary methods. In particular, the use of carbon and nitrogen isotopes of lipids along with environmental DNA have a great potential to identify the source and quantify the contribution of different primary producers to sedimentary organic carbon in marine ecosystems. Despite the promising potential of these new techniques, further research is needed to validate them. This critical overview can inform future research to help underpin methodologies for the implementation of blue carbon focused climate change mitigation schemes.